2018
DOI: 10.1186/s13014-018-1047-5
|View full text |Cite
|
Sign up to set email alerts
|

PSMA-PET based radiotherapy: a review of initial experiences, survey on current practice and future perspectives

Abstract: 68Gallium prostate specific membrane antigen (PSMA) ligand positron emission tomography (PET) is an increasingly used imaging modality in prostate cancer, especially in cases of tumor recurrence after curative intended therapy. Owed to the novelty of the PSMA-targeting tracers, clinical evidence on the value of PSMA-PET is moderate but rapidly increasing. State of the art imaging is pivotal for radiotherapy treatment planning as it may affect dose prescription, target delineation and use of concomitant therapy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 68 publications
1
27
0
1
Order By: Relevance
“…Although these previous publications have investigated the correlation between GS and SUV, the correlation between GS and more sophisticated PET image features has not yet been evaluated. First studies analyzed the value of PSMA PET in detection of lymph nodes metastases in patients with primary PCa 15, 16. Maurer et al reported a sensitivity of 0.66 and a specificity of 0.99 for PSMA PET in lymph node detection 17.…”
Section: Introductionmentioning
confidence: 99%
“…Although these previous publications have investigated the correlation between GS and SUV, the correlation between GS and more sophisticated PET image features has not yet been evaluated. First studies analyzed the value of PSMA PET in detection of lymph nodes metastases in patients with primary PCa 15, 16. Maurer et al reported a sensitivity of 0.66 and a specificity of 0.99 for PSMA PET in lymph node detection 17.…”
Section: Introductionmentioning
confidence: 99%
“… 7,8 It has been suggested by some groups that PSMA PET/CT should be the gold standard for imaging in biochemical recurrent prostate cancer as well as having utility in staging and assessing treatment response. 9 …”
Section: Discussionmentioning
confidence: 99%
“…Our departmental policy is that evidence of pelvic lymph nodes should lead to irradiation of the pelvic lymphatic basin according to the Radiation Therapy Oncology Group consensus recommendations on delineation of pelvic lymphatic pathways (40) with a simultaneous boost to the PET-positive lymph nodules and additional androgen deprivation therapy. Interestingly, there is strong controversy on the best therapeutic approach in cases of positive lymph nodes, with some centers opting for stereotactic body radiotherapy to the PET-positive lymph nodes only (48). Having recently presented our data on outcome in patients with biochemical recurrence treated on the basis of the results of 68 Ga-PSMA PET/CT (9), we believe that eradicating microscopic spread to surrounding lymphatic pathways, dose escalation to macroscopic tumor burden, and at least concomitant use of androgen deprivation therapy might be more favorable than stereotactic body radiotherapy of PET-positive nodes only.…”
Section: Discussionmentioning
confidence: 99%